PERSEPSI MAHASISWA TERHADAP BRAND IMAGE ROKOK MARLBORO PADA KAMPUS UKIM AMBON - P.M.Sirait, Jimmy; Soplanit, Alfionita (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to determine students' perceptions of the brand image of Marlboro cigarettes, one of the world's most famous cigarette brands. This research was conducted using a quantitative approach through a survey involving students from various universities in Indonesia. Data was collected using a questionnaire that focused on brand image dimensions, namely brand associations, brand image, and perceptions of Marlboro cigarette advertising. The research results show that students' perceptions of the Marlboro brand image are influenced by various factors, including the influence of advertising, brand identity, and socio-cultural factors related to cigarette consumption among the public. These findings provide insight into how students view the Marlboro brand and can be the basis for future cigarette marketing strategies, even taking into account the increasingly stringent regulatory aspects of the marketing of tobacco products.